An overview on spalling behavior, mechanism, residual strength and microstructure of fiber reinforced concrete under high temperatures - Gong, Fang; Jiang, Xi; Gamil, Yaser; Iftikhar, Bawar; Thomas, Blessen Skariah (Frontiers in Materials, 2023)
Recent research has shown that the incorporation of fibres, such as steel and polypropylene fibres, in concrete can significantly improve its resistance to spalling under high-temperature conditions. However, the reported outcomes of studies on the spalling performance of Fibre Reinforced Concrete (FRC) vary significantly due to differences in cementitious matrix and fibre types, mix design, and testing techniques. Existing review studies have struggled to systematically and precisely consolidate the diverse aspects of the literature. To address these limitations, this paper adopts the latest approach for mining, processing, and analyzing data to interpret bibliographic data on the fire resistance of FRC. The primary objective of this study is to comprehensively explore the viability of FRC as a fire-resistant and refractory material. In pursuit of this goal, the paper thoroughly reviews various aspects of FRC behavior at elevated temperatures, including pore pressure behaviors. Moreover, this review also discusses spalling behaviors, mechanisms, and residual mechanical properties under high temperatures. The microstructural analysis of FRC is also discussed comprehensively to gain an in-depth understanding of its behavior under elevated temperatures. By analyzing available data, this study aims to shed light on the potential of FRC as a suitable material for resisting spalling in high-temperature scenarios. Additionally, the research delves into prospects and challenges in achieving sustainable FRC with enhanced spalling resistance, considering both material and structural levels.